Ergonomic Properties of Traditional Malay Furniture - Zainal Abidin, Nabilah; Nafida Raja Shahminan, Raja; Khair Ibrahim, Fawazul (International Journal of Engineering and Technology, 2018)
Furniture is part and parcel of everyday life in any population. Therefore usage of furniture is considered a significant factor in improving oneâ€™s health and lifestyle. This paper studies on the ergonomic properties that can be found in various Traditional Malay furniture, inside Traditional Malay Houses of Malaysia. The objective of this study is to calculate anthropometric measurements of the Traditional Malays, in order to define the ergonometric properties of Traditional Malay furniture. Primary data for this study were taken from measured drawings of selected houses archived in The Centre for the Study of Built Environment in the Malay World (KALAM), Universiti Teknologi Malaysia (UTM). The method used in this study comprises of three dimensional (3D) rendering of the houses recreated using the program 3DStudioMax. 3D models of humans and interiors of the houses were created to help in defining and calculating the ergonometric properties of the furniture found inside each houses. The findings of this study will help in defining a standard of ergonomics that can be used in the production of furniture in Malaysia, which in turn will significantly increase the status of living and longevity of the people.Â Â